Testbed for experimental analysis on seamless evolution architectures from GPON to high capacity WDM-PON. (6th July 2010) - Berrettini, G.; Giorgi, L.; Ponzini, F.; Cavaliere, F.; Ghiggino, P.; Poti, L.; Bogoni, A.
The reuse of existing infrastructure whilst keeping unaffected the legacy equipment is a crucial feature for the evolution of gigabit passive optical networks (GPONs) towards higher capacity wavelength division multiplexed-passive optical networks (WDM-PONs). In this paper, a testbed for the evaluation of simple and cost effective GPON evolutions will be presented. A comprehensive set of WDM-PON architectures based on remote wavelengths distribution and wavelengths reuse for upstream (US) transmission will be proposed. Both 2.5 Gb/s and 10 Gb/s (symmetric traffic) have been taken into account and experimentally evaluated in terms of bit error rate (BER) on the same testing bench. System perspectives and limitations are also discussed.